2022
DOI: 10.1093/infdis/jiac108
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Prevalence of Anal and Cervical Human Papillomavirus Infection and High-Grade Lesions in 11 177 Women by Human Immunodeficiency Virus Status: A Collaborative Pooled Analysis of 26 Studies

Abstract: Background Age-specific data on anal, and corresponding cervical, human papillomavirus (HPV) infection are needed to inform female anal cancer prevention. Methods We centrally re-analyzed individual-level data from 26 studies reporting HPV prevalence in paired anal and cervical samples by HIV status and age. For women living with HIV (WLWH) with anal high-grade squamous intraepithelial lesions (HSIL+), we also investigated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…There is accumulating evidence that some biomarkers, like HPV16, could stratify the heterogeneous group of AIN2/3 into those that are more or less likely to progress to cancer. 2,57 Similarly, other biomarkers such as p16/Ki-67 and methylation could be considered to improve anal disease classification in future analyses. A second limitation of this study is that due to the urgency of generating evidence for ongoing guidelines efforts, we did not obtain individual-level data from studies which would allow to evaluate more test combinations such as anal cytology and HPV16/18 genotyping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that some biomarkers, like HPV16, could stratify the heterogeneous group of AIN2/3 into those that are more or less likely to progress to cancer. 2,57 Similarly, other biomarkers such as p16/Ki-67 and methylation could be considered to improve anal disease classification in future analyses. A second limitation of this study is that due to the urgency of generating evidence for ongoing guidelines efforts, we did not obtain individual-level data from studies which would allow to evaluate more test combinations such as anal cytology and HPV16/18 genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CIN2 in cervical cancer screening, AIN2 is a poorly reproducible, heterogenous disease category, whereas AIN3 is likely a better surrogate of anal cancer risk. There is accumulating evidence that some biomarkers, like HPV16, could stratify the heterogeneous group of AIN2/3 into those that are more or less likely to progress to cancer 2,57 . Similarly, other biomarkers such as p16/Ki‐67 and methylation could be considered to improve anal disease classification in future analyses.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast to cervical HPV16 prevalence, which declined with age, the anal HPV16 prevalence was constant with aging. 11 The number of studies describing the prevalence of anal HPV infection and anal HSIL in solid organ transplant recipients is much lower than the number of such studies in people living with HIV. A meta-analysis showed that the prevalence of HPV16 was 4% and that of anal HSIL was 5% (approximately 4 times lower than in MSM living with HIV).…”
Section: Epidemiology Of Anal Hpv and Anal Intraepithelial Neoplasiamentioning
confidence: 94%
“…Regarding HPV clearance in men, another large study (a pooled analysis of 34 longitudinal studies) confirmed that the clearance of HPV16 was lower for people living with HIV 10 . A pooled analysis of 26 studies showed that in women living with HIV, the prevalence of anal HPV16 was 12%, higher than in the cervix (9%), and the prevalence of anal HSIL was 6% 11 . In contrast to cervical HPV16 prevalence, which declined with age, the anal HPV16 prevalence was constant with aging 11 …”
Section: Epidemiology Of Anal Hpv and Anal Intraepithelial Neoplasiamentioning
confidence: 95%
See 1 more Smart Citation